Education policy and intergenerational transfers in equilibrium - Brant Abbott; Giovanni Gallipoli; Costas Meghir; Giovanni L. Violante (Institute for Fiscal Studies (IFS), 2018)
This paper examines the equilibrium effects of alternative financial aid policies intended to promote college participation. We build an overlapping generations life cycle model with education, labor supply, and consumption/saving decisions. Cognitive and non-cognitive skills of children depend on the cognitive skills and education of parents, and affect education choice and labor market outcomes. Driven by both altruism and paternalism, parents make transfers to their children which can be used to fund education, supplementing grants, loans and the labor supply of the children themselves during college. The crowding out of parental transfers by government programs is sizable and thus cannot be ignored when designing policy. The current system of federal aid is valuable: removing either grants or loans would each reduce output by 2% and welfare by 3% in the long-run. An expansion of aid towards ability-tested grants would be markedly superior to either an expansion of student loans or a labor tax cut. This result is, in part, due to the complementarity between parental education and ability in the production of skills of future generations.
Keywords: E24; I22; J23; J24; 330; Ability Transmission; Altruism; Credit Constraints; Education; Equilibrium; Financial Aid; Intergenerational Transfers; Paternalism; Studienfinanzierung; Intergenerationale Übertragung; Bildungspolitik; Overlapping Generations; Agentenbasierte Modellierung; Theorie; USA